A PBT composite material and preparation method thereof

By modifying PBT flame retardant and porous starch adsorbing antioxidants, the problems of poor compatibility of halogen-free flame retardant and easy consumption of antioxidants in PBT composite materials are solved, achieving better flame retardant, antioxidant and antibacterial effects, and reducing environmental pollution.

CN118931130BActive Publication Date: 2025-04-11KUNSHAN POLYSTAR ENG PLASTICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411287111.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-04-11
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing PBT composite materials have poor compatibility when introducing halogen-free flame retardant, resulting in poor flame retardant effect. At the same time, antioxidants are easily consumed, and the toxicity of antibacterial agents and environmental pollution problems have not been effectively solved.

Method used

The preparation method of modified PBT flame retardant is adopted to chemically modify PBT with halogen-free flame retardant through photoinitiation reaction and catalyst action to improve its compatibility with PBT; at the same time, porous starch is used to adsorb antioxidants to extend their service life; and antibacterial agents are prepared by oxidizing materials such as sodium alginate and polylysine to improve the antibacterial effect.

Benefits of technology

It significantly improves the compatibility of halogen-free flame retardant with PBT materials, optimizes flame retardant performance, extends the service life of antioxidants, improves the antibacterial effect, reduces the use of heavy metal ions, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118931130B_ABST
    Figure CN118931130B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer plastics, and in particular to a PBT composite material and a preparation method thereof. The PBT composite material is prepared from the following raw materials in parts by weight: 65 to 90 parts of polybutylene terephthalate, 5 to 30 parts of modified PBT flame retardant, 3 to 5 parts of antibacterial agent, 0.2 to 0.8 parts of compatibilizer, and 1 to 2 parts of porous starch-antioxidant. The present invention uses a chemical method to modify the oligomeric PBT, impart flame retardancy to it, and then blends it with PBT to solve the problem that the current PBT composite material can only introduce limited halogen-free flame retardants and the compatibility of halogen-free flame retardants with PBT is poor; the antioxidant is adsorbed using porous starch to avoid the antioxidant being completely consumed in a short time, so that the antioxidant can more effectively protect the material, improve stability, and extend the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer plastics, and in particular relates to a PBT composite material and a preparation method thereof. Background Art

[0002] Polybutylene terephthalate (PBT) is a milky white translucent to opaque crystalline thermoplastic polyester resin made by condensation of 1,4-butanediol and terephthalic acid through a mixing process. It has very good chemical stability, mechanical strength, electrical insulation properties and thermal stability. PBT plastic has fast crystallization speed, good fluidity, lower mold temperature requirements than other engineering plastics, and is easy to process and shape. It is widely used in electronic appliances, switch parts, household appliances and electronic watch housings.

[0003] The preparation method of antibacterial PBT mainly forms by adding a small amount of antibacterial agent blending compound at present, and its effective ingredient is antibacterial agent, and these antibacterial agents are divided into inorganic antibacterial agent and organic antibacterial agent, because inorganic antibacterial agent is stable in plastics heat forming process, application is more general, but most of inorganic antibacterial agents are heavy metal ions, such as nano silver, which is larger to human toxicity, and can cause environmental pollution. The main variety of organic antibacterial agent has fragrant aldehyde, ethyl vanillin compounds, quaternary ammonium salts and biguanides etc., and the organic antibacterial agent has poor temperature resistance, and long-term use has dissolution, precipitation phenomenon. However, the viscosity of existing modified grade polybutylene terephthalate is higher, and PBT specific gravity is larger, and it is more difficult to obtain high-filled PBT composite material, so the antibacterial material prepared with PBT resin is difficult to obtain good antibacterial effect.

[0004] At present, the preparation method of antioxidant PBT is mainly to add a small amount of antioxidants to blend and compound, and its effective ingredient is antioxidants, which include phenolic antioxidants, phosphite antioxidants, and thioester antioxidants. However, when antioxidants are directly added to PBT using the existing blending and compounding method, the antioxidant-containing PBT material is prone to consume the antioxidant in a short time due to the large contact area and long contact time between the antioxidant and the air, resulting in the antioxidant in the PBT composite material. The role of the antioxidant in protecting the material, improving stability, and extending the service life is relatively limited.

[0005] At present, the preparation method of flame-retardant PBT is mainly through the addition of flame retardants and compounding. Its effective ingredient is flame retardant, which includes brominated flame retardants and halogen-free flame retardants. Brominated flame retardants have good flame retardant effects, but they will release a large amount of halides during the decomposition process, which will cause harm to the environment and human body, which is contrary to the current environmental protection requirements; halogen-free flame retardants do not contain halogens, so they will not release halides, have less pollution to the environment, and are more in line with current environmental protection requirements. However, compared with brominated flame retardants, the flame retardant effect of halogen-free flame retardants may be slightly inferior. In order to achieve the same flame retardant effect, halogen-free flame retardants may need to be added in larger amounts, and the compatibility of halogen-free flame retardants with most plastics is poor. How to improve the compatibility of halogen-free flame retardants with most plastics while introducing sufficient amounts of halogen-free flame retardants is a key issue that needs to be solved urgently. Summary of the invention

[0006] In order to overcome the deficiencies of the prior art, one of the objects of the present invention is to provide a method for preparing a PBT composite material, which significantly improves the compatibility between the PBT material and a large amount of halogen-free flame retardant while incorporating the halogen-free flame retardant.

[0007] One of the purposes of the present invention is achieved by the following technical solution:

[0008] A method for preparing a PBT composite material is prepared by extrusion granulation of the following raw materials in parts by weight: 65-90 parts of polybutylene terephthalate, 5-30 parts of modified PBT flame retardant, 3-5 parts of antibacterial agent, 0.2-0.8 parts of compatibilizer, and 1-2 parts of porous starch-antioxidant.

[0009] Furthermore, the preparation process of the modified PBT flame retardant comprises the following steps:

[0010]

[0011] (1) a PBT polyester prepolymer having a degree of polymerization of 5 to 20 is reacted with a glycidyl methacrylate solution and a photoinitiator under light for 16 to 48 hours. After the reaction is completed, the reaction solution is post-treated to obtain compound 1;

[0012] (2) reacting the compound 1 in step (1) with diethylene glycol at 45-60° C. for 6-12 hours in the presence of a catalyst. After the reaction is complete, collecting the product, washing it, and drying it to obtain compound 2;

[0013] (3) reacting the compound 2 described in step (2), phosphoric acid and urea at 100-130° C. for 6-24 hours. After the reaction is completed, collecting the product and washing and drying it to obtain a modified PBT flame retardant.

[0014] Furthermore, the photoinitiator in step (1) is benzophenone, and the mass ratio of the PBT polyester prepolymer with a degree of polymerization of 5 to 20, glycidyl methacrylate and the photoinitiator is 75: (20 to 30): (0.2 to 0.3).

[0015] Furthermore, the catalyst in step (2) is sulfuric acid, and the usage ratio of compound 1, diethylene glycol and sulfuric acid is 20 g: (100-200) mL: (1-2) g.

[0016] Furthermore, in step (3), the mass ratio of the compound 2, phosphoric acid and urea is 35:(20-30):(12-18.5); and the detergent used for washing is a mixture of ethanol and deionized water in a volume ratio of 1:1.

[0017] Furthermore, the preparation process of the antibacterial agent includes the following steps: taking equal volumes of oxidized sodium alginate solution and polylysine solution and mixing them, then adding silver ion reagent to obtain a mixed solution, reacting the mixed solution with CaCl2 solution at 4-7°C for 12-16h, and after the reaction is completed, collecting the product and washing and drying it to obtain the antibacterial agent.

[0018] Furthermore, the porous starch-antioxidant is prepared by mixing a tea polyphenol aqueous solution with porous starch for reaction for 2.5 to 3 hours, followed by washing and drying; the mass ratio of the porous starch to the tea polyphenol is 1:(0.1 to 0.3).

[0019] Furthermore, the compatibilizer is one of a silane coupling agent and a titanate coupling agent; and the silver ion reagent is silver nitrate.

[0020] A second object of the present invention is to provide a PBT composite material.

[0021] The second object of the present invention is achieved by adopting the following technical solution:

[0022] The PBT composite material is prepared according to the above preparation method.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention uses a chemical method to modify oligomeric PBT to make it flame retardant, and then blends it with PBT to prepare a PBT composite material. The present invention not only solves the problem that only limited halogen-free flame retardants can be introduced into current PBT composite materials, but also solves the problem that current halogen-free flame retardants have poor compatibility with PBT, optimizes and improves the flame retardant performance of PBT composite materials in the field of automotive parts, and achieves more excellent safety performance.

[0025] 2. The present invention uses porous starch to adsorb antioxidants, which solves the problem that the current antioxidants have a large contact area with the air and a long contact time, causing them to be completely consumed in a short time, so that the antioxidants can more effectively protect the materials, improve stability, and extend the service life of the materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the synthesis route of the modified PBT flame retardant of the present invention;

[0027] Figure 2 It is an infrared schematic diagram of the intermediate compound 1 of the modified PBT flame retardant of the present invention. DETAILED DESCRIPTION

[0028] Below, in conjunction with the accompanying drawings and specific embodiments, the present invention is further described. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0029] Example 1

[0030] A PBT composite material, its preparation process comprises the following steps:

[0031] (1) Preparation of modified PBT flame retardant

[0032] The preparation route of the modified PBT flame retardant of the present invention is as follows: Figure 1 As shown, the specific steps are:

[0033] A: Take 50mL of 0.3g / mL n-butanol solution of glycidyl methacrylate, add 75g of PBT polyester prepolymer with a degree of polymerization of 5-20 to obtain a mixed solution; add 0.15g of benzophenone to the mixed solution in a light-proof environment, stir evenly, turn on the ultraviolet lamp, the intensity of the ultraviolet lamp is 300W, and the light reaction is carried out for 16 hours; after the reaction is completed, the reaction liquid is distilled by negative pressure, the crude product remaining in the distillation flask is taken, the crude product is collected and washed with deionized water in an ultrasonic water bath at room temperature for 5 times, each washing for 5 minutes. Then the product is dried in a vacuum oven at 30°C for 5 hours to obtain compound 1.

[0034] B: 20 ​​g of compound 1 was placed in 200 mL of diethylene glycol (DEG) solution containing 0.01 g / mL sulfuric acid (H2SO4), and reacted at 50°C in a shaker with a rotation speed of 100 rpm for 8 h; after the reaction, the product was collected and washed with deionized water in an ultrasonic water bath at room temperature for 5 times, each washing for 5 min. The product was then dried in a vacuum oven at 30°C for 5 h to obtain compound 2.

[0035] C: Take 20g of phosphoric acid and put it in a reaction bottle, then add 35g of compound 2 into the reaction bottle, stir it with a glass rod and put it into a constant temperature heating magnetic stirrer, heat it to 120℃, continue stirring and react for 24h, then lower the reaction temperature to 100℃, add 12g of urea to the reaction bottle in batches, after the addition of urea, mix the system with mechanical stirring, then heat the constant temperature heating magnetic stirrer to 120℃ and continue the reaction until the pH of the mixture is 6, then terminate the reaction to obtain a crude product; then wash it 5 times with a mixture of ethanol and deionized water in a volume ratio of 1:1 in an ultrasonic water bath at room temperature, each washing for 5min, and vacuum dry it to obtain a modified PBT flame retardant.

[0036] The IR graph of the modified PBT flame retardant is as follows: Figure 2 As shown, at 1153cm -1 (ester group), 910cm -1 (epoxy), 849cm -1 There is absorption at (epoxy group), which indicates that the modified PBT flame retardant is successfully prepared in the present invention.

[0037] (2) Preparation of antibacterial agent

[0038] Weigh 0.015 g of oxidized sodium alginate and 2 g of polylysine, respectively, and add them into 10 mL of deionized water to obtain an oxidized sodium alginate solution and a polylysine solution; mix the oxidized sodium alginate solution and the polylysine solution in equal volumes, then add 2 mg of AgNO3, and ultrasonically treat the solution to obtain Ag + / oxidized sodium alginate / poly-lysine mixture; at 4 °C to Ag + 2 wt % CaCl2 was added to the mixture of sodium alginate / oxidized sodium alginate / polylysine and cross-linked for 16 h. After the reaction was completed, the product was collected and rinsed with deionized water to remove excess CaCl2, and then freeze-dried for 48 hours to obtain an antibacterial agent.

[0039] (3) Preparation of porous starch-tea polyphenols

[0040] A 5 mg / mL tea polyphenol solution was prepared with deionized water as solvent, 1 g of porous corn starch was weighed, 20 mL of tea polyphenol solution was added thereto, and the mixture was stirred for 3 h in a sealed and light-proof environment (room temperature); after the reaction, the reaction solution was centrifuged for 15 min at a rate of 4000 rpm, the precipitate was collected, washed 3 times with water, and dried in a vacuum dryer for 10 h, and then ground to obtain porous starch-tea polyphenols.

[0041] (4) Preparation of PBT composite materials

[0042] Weigh the following materials by weight: 90 parts of polybutylene terephthalate, 5 parts of modified PBT flame retardant, 3.8 parts of antibacterial agent, 0.2 parts of titanate coupling agent, and 1 part of porous starch-tea polyphenol. Mix the above materials in a high-speed mixer for 10 minutes and place them in a twin-screw extruder. After melt mixing, extrusion and granulation, a PBT composite material is obtained. The process parameters of the twin-screw extruder are set as follows: the temperature of zone 1 is 120-140°C, the temperature of zone 2 is 160-190°C, the temperature of zone 3 is 190-210°C, the temperature of zone 4 is 210-230°C, the temperature of zone 5 is 210-230°C, the temperature of zone 6 is 210-230°C, and the temperature of zone 7 is 230-250°C; the main engine speed is 300-350rpm.

[0043] Example 2

[0044] A PBT composite material, its preparation process comprises the following steps:

[0045] (1) Preparation of modified PBT flame retardant

[0046] The preparation route of the modified PBT flame retardant of the present invention is as follows: Figure 1 As shown, the specific steps are:

[0047] A: Take 50mL of 0.2g / mL n-butanol solution of glycidyl methacrylate, add 75g of PBT polyester prepolymer with a degree of polymerization of 5-20 to obtain a mixed solution; add 0.2g of benzophenone to the mixed solution in a light-proof environment, stir it evenly, turn on the ultraviolet lamp, the intensity of the ultraviolet lamp is 250W, and the light reaction is carried out for 28h; after the reaction is completed, the reaction liquid is distilled by negative pressure, the crude product remaining in the distillation flask is taken, the crude product is collected and washed with deionized water in an ultrasonic water bath at room temperature for 5 times, each washing for 5min. Then the product is dried in a vacuum oven at 30°C for 5h to obtain compound 1.

[0048] B: 20 ​​g of compound 1 was placed in 100 mL of diethylene glycol (DEG) solution containing 0.02 g / mL sulfuric acid (H2SO4), and reacted at 45°C in a shaker with a rotation speed of 120 rpm for 12 h to obtain a reaction solution; after the reaction, the product was collected and washed with deionized water in an ultrasonic water bath at room temperature for 5 times, each washing for 5 min. The product was then dried in a vacuum oven at 40°C for 4 h to obtain compound 2.

[0049] C: Take 30g of phosphoric acid and put it in a reaction bottle, then add 35g of compound 2 into the reaction bottle, stir it with a glass rod, put it into a constant temperature heating magnetic stirrer, heat it to 130°C, continue stirring to react for 16h, then lower the reaction temperature to 100°C, add 18.5g of urea to the reaction bottle in batches, after the addition of urea, mix the system with mechanical stirring, then heat the constant temperature heating magnetic stirrer to 130°C and continue the reaction until the pH of the mixture is 6, then terminate the reaction to obtain a crude product; then wash it 5 times with a mixture of ethanol and deionized water in a volume ratio of 1:1 in an ultrasonic water bath at room temperature, each washing for 5 minutes, and after vacuum drying, obtain a modified PBT flame retardant.

[0050] (2) Preparation of antibacterial agent

[0051] Weigh 0.02 g of oxidized sodium alginate and 2.5 g of polylysine, add them into 10 mL of deionized water, respectively, to obtain an oxidized sodium alginate solution and a polylysine solution; mix the oxidized sodium alginate solution and the polylysine solution in equal volumes, then add 3 mg of AgNO3, and ultrasonically treat the solution to obtain Ag + / oxidized sodium alginate / poly-lysine mixture; at 5 ° C to Ag + 3 wt % CaCl 2 was added to the mixture of sodium alginate / oxidized sodium alginate / polylysine and cross-linked for 16 h. After the reaction was completed, the product was collected and rinsed with deionized water to remove excess CaCl 2, and then freeze-dried for 48 hours to obtain an antibacterial agent.

[0052] (3) Preparation of porous starch-tea polyphenols

[0053] A tea polyphenol solution with a mass concentration of 10 mg / mL was prepared with deionized water as the solvent, 1 g of porous corn starch was weighed, 20 mL of the tea polyphenol solution was added thereto, and the mixture was stirred for 2.8 h in a sealed and light-proof (room temperature) environment; after the reaction, the reaction solution was centrifuged for 15 min at a rate of 3000 rpm, the precipitate was collected, washed 3 times with water, and dried in a vacuum dryer for 10 h, and then ground to obtain porous starch-tea polyphenols.

[0054] (4) Preparation of PBT composite materials

[0055] Step (4) of this embodiment is basically the same as step (4) of embodiment 1, except for the material ratio of preparing the PBT composite material. The weight ratio of the materials in this embodiment is: 65 parts of polybutylene terephthalate, 30 parts of modified PBT flame retardant, 3 parts of antibacterial agent, 0.8 parts of silane coupling agent, and 1.2 parts of porous starch-antioxidant.

[0056] Example 3

[0057] A PBT composite material, its preparation process comprises the following steps:

[0058] (1) Preparation of modified PBT flame retardant

[0059] The preparation route of the modified PBT flame retardant of the present invention is as follows: Figure 1 As shown, the specific steps are:

[0060] A: Take 100mL of 0.2g / mL n-butanol solution of glycidyl methacrylate, add 75g of PBT polyester prepolymer with a polymerization degree of 5-20 to obtain a mixed solution; add 0.3g of benzophenone to the mixed solution in a light-proof environment, stir evenly, turn on the ultraviolet lamp, the intensity of the ultraviolet lamp is 300W, and the light reaction is carried out for 48h; after the reaction is completed, the reaction liquid is distilled by negative pressure, the remaining crude product in the distillation flask is taken, the crude product is collected and washed with deionized water in an ultrasonic water bath at room temperature for 5 times, each washing for 5min. Then the product is dried in a vacuum oven at 30°C for 5h to obtain compound 1.

[0061] B: 20 ​​g of compound 1 was placed in 150 mL of diethylene glycol (DEG) solution containing 0.01 g / mL sulfuric acid (H2SO4), and reacted at 60°C in a shaker at 90 rpm for 6 h to obtain a reaction solution; after the reaction, the product was collected and washed with deionized water in an ultrasonic water bath at room temperature for 5 times, each washing for 5 min. The product was then dried in a vacuum oven at 35°C for 4 h to obtain compound 2.

[0062] C: Take 25g of phosphoric acid and put it in a reaction bottle, then add 35g of compound 2 into the reaction bottle, stir it with a glass rod, put it into a constant temperature heating magnetic stirrer, heat it to 125°C, continue stirring and react for 24h, then lower the reaction temperature to 100°C, add 15.4g of urea to the reaction bottle in batches, after the addition of urea, mix the system with mechanical stirring, then heat the constant temperature heating magnetic stirrer to 125°C and continue the reaction until the pH of the mixture is 6, then terminate the reaction to obtain a crude product; then wash it 5 times with a mixture of ethanol and deionized water in a volume ratio of 1:1 in an ultrasonic water bath at room temperature, each washing for 5 minutes, and after vacuum drying, obtain a modified PBT flame retardant.

[0063] (2) Preparation of antibacterial agent

[0064] Weigh 0.025 g of oxidized sodium alginate and 3 g of polylysine, respectively, and add them into 10 mL of deionized water to obtain an oxidized sodium alginate solution and a polylysine solution; mix the oxidized sodium alginate solution and the polylysine solution in equal volumes, then add 5 mg of AgNO3, and ultrasonically treat the solution to obtain Ag + / oxidized sodium alginate / poly-lysine mixture; at 7 ° C to Ag + 5 wt % CaCl 2 was added to the mixture of sodium alginate / polylysine / oxidized sodium alginate and cross-linked for 12 h. After the reaction was completed, the product was collected and rinsed with deionized water to remove excess CaCl 2, and then freeze-dried for 48 hours to obtain an antibacterial agent.

[0065] (3) Preparation of porous starch-tea polyphenols

[0066] A tea polyphenol solution with a mass concentration of 15 mg / mL was prepared with deionized water as the solvent, 1 g of porous corn starch was weighed, 20 mL of the tea polyphenol solution was added thereto, and the mixture was stirred for 2.5 h in a sealed and light-proof (room temperature) environment; after the reaction, the reaction solution was centrifuged for 15 min at a rate of 3500 rpm, the precipitate was collected, washed 3 times with water, and dried in a vacuum dryer for 10 h, and then ground to obtain porous starch-tea polyphenols.

[0067] (4) Preparation of PBT composite materials

[0068] Step (4) of this embodiment is basically the same as step (4) of embodiment 1, except for the material ratio of preparing the PBT composite material. The material mass ratio of this embodiment is: 80 parts of polybutylene terephthalate, 14 parts of modified PBT flame retardant, 3.5 parts of antibacterial agent, 0.5 parts of silane coupling agent, and 2 parts of porous starch-tea polyphenols.

[0069] Comparative Example 1

[0070] A PBT composite material, the preparation method of which is substantially the same as that of Example 1, except that step (1) is omitted and diphenyl phosphate in an amount equal to that of the modified PBT flame retardant is directly added during the preparation of the PBT composite material.

[0071] Comparative Example 2

[0072] A PBT composite material, the preparation method of which is basically the same as that of Example 1, except that step (2) is omitted, and polylysine in an amount equal to that of the antibacterial agent is directly added during the preparation of the PBT composite material.

[0073] Test Example 1

[0074] The PBT composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were injection molded into standard specimens on an injection molding machine, and flame retardant properties, antibacterial properties and mechanical properties were tested; wherein, the flame retardant property test was tested with reference to GB / T2408-2008 standard; the antibacterial property test was tested with reference to the antibacterial rate experiment using the plate count method (J. Food Sci. 2012, 77, 280-286); the mechanical property-notched impact strength was tested with reference to GB / T1043.1-2008 standard, the mechanical property-tensile strength was tested with reference to GB / T1040.5-2008 standard, and the mechanical property-flexural strength was tested with reference to GB / T9341-2008 standard. The above test results are shown in Table 1.

[0075] Table 1 Performance test results of PBT composite materials of Examples 1-3 and Comparative Examples 1-2

[0076]

[0077] As can be seen from Table 1, the PBT composite materials of Examples 1-3 and Comparative Examples 1-2 are all antibacterial, and the antibacterial effect of Comparative Example 2 is poor, which shows that the antibacterial effect of the antibacterial agent prepared by the present invention is better than that of ordinary polylysine. The flame retardant properties of Examples 1-3 and Comparative Examples 1-2 all reach the V-0 level, but the precipitation resistance of Comparative Example 1 is poor. This is because the diphenyl phosphate used in Comparative Example 1 has a rough surface when used in PBT resin and has poor compatibility with PBT resin. The modified flame retardant prepared in the present application is evenly dispersed in the PBT matrix, has a smooth surface, and has no precipitation phenomenon, indicating that it has better compatibility. In addition, compared with Examples 1-3, Comparative Example 1 uses the existing flame retardant diphenyl phosphate, and the mechanical properties of the PBT material obtained are also worse.

[0078] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a PBT composite material, characterized in that: The modified PBT flame retardant is prepared by extrusion granulation of the following raw materials in parts by weight: 65-90 parts of polybutylene terephthalate, 5-30 parts of modified PBT flame retardant, 3-5 parts of antibacterial agent, 0.2-0.8 parts of compatibilizer, and 1-2 parts of porous starch-antioxidant; the preparation process of the modified PBT flame retardant includes the following steps: (1) a PBT polyester prepolymer having a degree of polymerization of 5 to 20 is reacted with a glycidyl methacrylate solution and a photoinitiator under light for 16 to 48 hours. After the reaction is completed, the reaction solution is post-treated to obtain compound 1; (2) reacting the compound 1 in step (1) with diethylene glycol at 45-60° C. for 6-12 hours in the presence of a catalyst. After the reaction is complete, collecting the product, washing it, and drying it to obtain compound 2; (3) reacting the compound 2 described in step (2), phosphoric acid and urea at 100-130° C. for 6-24 hours. After the reaction is completed, collecting the product and washing and drying it to obtain a modified PBT flame retardant.

2. The method for preparing the PBT composite material according to claim 1, characterized in that: In step (1), the photoinitiator is benzophenone, and the mass ratio of the PBT polyester prepolymer with a degree of polymerization of 5 to 20, glycidyl methacrylate and the photoinitiator is 75: (20 to 30): (0.2 to 0.3).

3. The method for preparing the PBT composite material according to claim 1, characterized in that: The catalyst in step (2) is sulfuric acid, and the usage ratio of compound 1, diethylene glycol and sulfuric acid is 20 g: (100-200) mL: (1-2) g.

4. The method for preparing the PBT composite material according to claim 1, characterized in that: In step (3), the mass ratio of compound 2, phosphoric acid and urea is 35:(20-30):(12-18.5); the detergent used for washing is a mixture of ethanol and deionized water in a volume ratio of 1:

1.

5. The method for preparing the PBT composite material according to claim 1, characterized in that: The preparation process of the antibacterial agent includes the following steps: taking equal volumes of oxidized sodium alginate solution and polylysine solution and mixing them, adding silver ion reagent to obtain a mixed solution, reacting the mixed solution with CaCl2 solution at 4-7°C for 12-16h, and after the reaction is completed, collecting the product and washing and drying it to obtain the antibacterial agent.

6. The method for preparing the PBT composite material according to claim 1, characterized in that: The porous starch-antioxidant is prepared by mixing a tea polyphenol aqueous solution with porous starch for reaction for 2.5 to 3 hours, followed by washing and drying; the mass ratio of the porous starch to the tea polyphenol is 1:(0.1 to 0.3).

7. The method for preparing the PBT composite material according to claim 5, characterized in that: The compatibilizer is one of a silane coupling agent and a titanate coupling agent; and the silver ion reagent is silver nitrate.

8. A PBT composite material prepared according to the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Phosphate-modified porous starch quantitative embedding tea polyphenol compound and preparation method and application thereof

    CN105105335A

  • Flame-retardant antibacterial polyurethane foam as well as preparation method and application thereof

    CN115286838A

  • Modified PBT plastic and injection molding method thereof

    CN116904003A

  • Antibacterial PBT material and preparation method thereof

    CN117586611A